Assessing knowledge management implementation at IWS, Mesiniaga Berhad / Rozilawati Razali - Razali, Rozilawati (2002)
Nowadays, the importance of Knowledge Management (KM) has been intensively discussed within the society. The management of knowledge is promoted as an important and necessary factor for every organisation to survive and maintain its competitive strength. Indeed, Knowledge and Knowledge Management appear to be regarded as increasingly important features for organisational survival. To remain at the forefront, organisations need a good capacity to retain, develop, organise, and utilise their employees' capabilities. The rise of the Knowledge Economy (K-Economy), one principally driven by information and knowledge, is attributed to the increased prominence of intellectual capital (IC) as a business asset. In future, it is believed that the organisation's IC is one of the most needed and essential assets. This paper is intended to relate the concepts of KM and IC to one of the local IT organisations, Mesiniaga Berhad. As the organisation has already implemented KM system since 1998, therefore, the paper focuses on its current system in order to assess the extent of the KM implementation. Besides, the paper also identifies the organisation's IC in order to know how it is valued and managed in the organisation. As the outcomes of the assessment, some recommendations and suggestions for improvement are also included in the paper for future enhancement.